2015
DOI: 10.1021/acs.chemmater.5b00665
|View full text |Cite
|
Sign up to set email alerts
|

Defect Control To Enhance Proton Conductivity in a Metal–Organic Framework

Abstract: A deep understanding of the structure of solid-state materials allows for a simplified process of design, synthesis, and characterization. One class of materials which highlights this process are metal−organic frameworks (MOFs), which are crystalline porous solids constructed from organic linkers connecting metal nodes. The crystalline nature of the MOF gives a picture of the internal structure of the solid, providing insight into the structure−property relationships for a desired application, while the combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(184 citation statements)
references
References 47 publications
8
175
1
Order By: Relevance
“…These factors could be the main reasons why Ti–UiO‐66‐H displayed much higher ODS activity (66.3 % yield of DBTO 2 ) than UiO‐66‐H. In comparison, as reported, there are many coordination unsaturated sites in the structure of UiO‐66‐D with crystal defects . Accordingly, UiO‐66‐D showed better ODS activity (50.7 % yield of DBTO 2 ) than UiO‐66‐H.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…These factors could be the main reasons why Ti–UiO‐66‐H displayed much higher ODS activity (66.3 % yield of DBTO 2 ) than UiO‐66‐H. In comparison, as reported, there are many coordination unsaturated sites in the structure of UiO‐66‐D with crystal defects . Accordingly, UiO‐66‐D showed better ODS activity (50.7 % yield of DBTO 2 ) than UiO‐66‐H.…”
Section: Resultsmentioning
confidence: 79%
“…In comparison, as reported, there are many coordination unsaturated sites in the structure of UiO-66-D with crystal defects. [40][41][42][43][44] are relativelyl arge, [7] the increasei ns urface area andp ore volumeo fU iO-66(Zr) after Ti ione xchange shoulda lso be factors for improving the catalytic activity of UiO-66(Zr) due to the enhancement of mass transfer ability.…”
Section: Relationship Between Structure and Catalytic Performancementioning
confidence: 99%
“…In fact, they found that the catalytic activity is a direct function of the number of defects, with MOF-808 being the best performing material, in agreement with its status of more defective compound. Defects were also harnessed to improve proton conduction in UiO-66, taking advantage of the increase in both pore volume and number of acidic sites upon creation of defects, with the aim of enhancing mobility of the charge carrier [122]. Defective samples were prepared either by using substoichiometric amounts of linker or by adding a modulator during the synthesis [AA or stearic acid (SA, Chart 2)].…”
Section: Brønsted Aciditymentioning
confidence: 99%
“…There are several strategies to achieve high proton conductivity in MOF materials, including incorporation of protonc arriers into pores or channels, [14][15][16][17][18] post-synthetic functionalizationo fc oordinately unsaturated metal sites, [19] varying the acidity of the pores by specific functional groups, [20] and control and modification of structurald efects. [21,22] To date, the proton-conducting properties of an umerousd ifferent oxalate-, [23,24] sulfate-, [25,26] carboxylate-based [27][28][29] MOFs have been investigated. Amongt he knownc onductive MOFs phosphonate-based materials are very promising for proton conductivity due to the ability of the phosphonatest oa ct as multitopic linkers through the coordination of three oxygen atoms to the metal sites or strong hydrogenbonding to protonc arrier molecules.…”
mentioning
confidence: 99%